The Marine Gastropod Crepidula fornicata Remains Resilient to Ocean Acidification Across Two Life History Stages - Reyes-Giler, Christopher L.; Benson, Brooke E.; Levy, Morgan; Chen, Xuqing; Pires, Anthony; Pechenik, Jan A.; Davies, Sarah W. (Frontiers in Physiology, 2021)
Rising atmospheric CO2 reduces seawater pH causing ocean acidification (OA). Understanding how resilient marine organisms respond to OA may help predict how community dynamics will shift as CO2 continues rising. The common slipper shell snail Crepidula fornicata is a resilient marine gastropod native to eastern North America and has been a successful invader along the western European coastline and elsewhere. To examine its potential resilience to OA, we conducted two controlled laboratory experiments. First, we examined several phenotypes and genome-wide gene expression of C. fornicata in response to pH treatments (7.5, 7.6, 8.0) throughout the larval stage and then tested how conditions experienced as larvae influenced juvenile stages (i.e. carry-over effects). Second, we examined genome-wide gene expression patterns of C. fornicata larvae in response to acute (4, 10, 24 and 48 hours) pH treatment (7.5, 8.0). Both C. fornicata larvae and juveniles exhibited resilience to OA and their gene expression responses highlight the role of transcriptome plasticity in this resilience. Larvae did not exhibit reduced growth under OA until they were at least 8 days old. These phenotypic effects were preceded by broad transcriptomic changes, which likely served as an acclimation mechanism for combating reduced pH conditions frequently experienced in littoral zones. Larvae reared in reduced pH conditions also took longer to become competent to metamorphose. In addition, while juvenile sizes at metamorphosis reflected larval rearing pH conditions, no carry-over effects in juvenile growth rates were observed. Transcriptomic analyses suggest increased metabolism under OA, which may indicate compensation in reduced pH environments. Time course transcriptomic analyses suggest energetic burdens experienced under OA eventually dissipate, allowing C. fornicata to reduce metabolic demands and acclimate to reduced pH. Carry-over effects from larval OA conditions were observed in juveniles; however, these effects were larger for more severe OA conditions and larvae reared in those conditions also demonstrated less transcriptome elasticity. This study highlights the importance of assessing the effects of OA across life history stages and demonstrates how transcriptomic plasticity may allow highly resilient organisms, like C. fornicata, to acclimate to reduced pH environments.